The Psychological Effect of Internet-Based Mindfulness-Based Stress Reduction on the Survivors of Breast Cancer During the COVID-19 - Kang, Chuanyuan; Sun, Shufang; Yang, Zhuangqing; Fan, Xinxin; Yuan, Jing; Xu, Li; Wei, Yujun; Tong, Huiqi; Yang, Jianzhong (Frontiers in Psychiatry, 2021)
Objective: To examine the efficacy and the role of engagement of an internet-based Mindfulness-based Stress Reduction (iMBSR) for breast cancer survivors (BCS) during the COVID-19 period from January to March in 2020 in China. Methods: A total of 48 BCS were divided into the absentees group and the iMBSR groups according to their attending to the standardized, group-based, 8-week iMBSR. Based on practice time, BCS in the iMBSR were categorized into three subgroups: group 1 (<30 min/day), group 2 (30-60 min/day), and group 3 (>60 min/day). In addition, participants were classified as partial attendees (less than 4 sessions) and completers (more than 4 sessions) of the iMBSR groups. All participants were evaluated for symptoms of depression, anxiety and insomnia at baseline, mid-intervention, and post-intervention. Results: After an 8-week iMBSR practice, at mid-intervention and post-intervention, participants in iMBSR group had significant improvement in scores and reduction rates of depression, anxiety and insomnia compared to absentees. Scores of depression and insomnia, reduction rates of depression at post-intervention, scores of anxiety, reduction rates of anxiety and insomnia at mid-intervention and post-intervention, had significant differences among subgroups of practice time. Daily practice time was positively related to reduction rates of depression, anxiety and insomnia at post-intervention in the iMBSR group. Conclusion: Internet-based MBSR showed efficacy in reducing psychological symptoms among BCS patients. For BCS participants, iMBSR practice has a potential dose–response efficacy, with a threshold of > 30 minutes daily practice for most optimal symptoms reduction.